Microvascular function in women with former gestational diabetes: A cohort study. (May 2017) - Charwat-Resl, Silvia; Yarragudi, Rajashri; Heimbach, Moritz; Leitner, Karoline; Leutner, Michael; Gamper, Jutta; Giurgea, Georgiana-Aura; Mueller, Markus; Koppensteiner, Renate; Gschwandtner, Michael E; Kautzky-Willer, Alexandra; Schlager, Oliver
Objective: In the long term, diabetes mellitus is potentially associated with the occurrence of microvascular damage. This study sought to assess whether a history of prior gestational diabetes mellitus is associated with long-term effects on the women's microcirculation. Methods: Within the scope of a long-term follow-up of the 'Viennese Post-Gestational Diabetes Project', women with prior gestational diabetes mellitus as well as women with previous pregnancy but with no history of gestational diabetes mellitus (controls) were enrolled in this cross-sectional study. Microvascular function was assessed by post-occlusive reactive hyperaemia using laser Doppler fluxmetry. Baseline perfusion, biological zero, peak perfusion, time to peak and recovery time were recorded and compared between both groups. Results: Microvascular function was assessed in 55 women with prior gestational diabetes mellitus (46.1 ± 4.6 years) and 32 women with previous pregnancy but without prior gestational diabetes mellitus (42.9 ± 5.3 years). The mean period of time between delivery and the assessment of microvascular function was 16.2 ± 5.2 years in women with prior gestational diabetes mellitus group and 14.2 ± 4.8 years in controls. Regarding microvascular function, baseline perfusion, biological zero, peak perfusion, time to peak and recovery time did not differ between women with prior gestational diabetes mellitus and controls (all p > 0.05). Conclusion: In the long term, microvascular function appears not to be impaired in women with prior gestational diabetes mellitus.